2019
DOI: 10.1167/iovs.18-25502
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Attenuates Proangiogenic Activity of Mononuclear Phagocytes: Implication in Choroidal Neovascularization

Abstract: Targeting b-adrenergic receptor signaling with propranolol has emerged as a potential candidate to counteract choroidal neovascularization (CNV). Little is known of its effect on macrophages, which play a critical role in CNV. We investigated the effect of propranolol on angiogenic response of mononuclear phagocytes (MPs). METHODS. The angiogenic effect of propranolol was evaluated in laser-induced CNV model. Mice received intraperitoneal injections of propranolol (6 mg/kg/d) or vehicle. CNV area and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…IL6 is increased after laser injury (Fig. 1 ), and reduced by propranolol 3 , 4 . We next investigated whether IL6 is necessary for propranolol-driven CNV blockade.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…IL6 is increased after laser injury (Fig. 1 ), and reduced by propranolol 3 , 4 . We next investigated whether IL6 is necessary for propranolol-driven CNV blockade.…”
Section: Resultsmentioning
confidence: 88%
“…Our group, and several other labs, have demonstrated that beta-adrenergic receptor blockade inhibits experimental CNV by 50–80% 3 – 8 . These findings led to a randomized, placebo controlled clinical trial.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Though no studies have investigated the effect of β-AR agonists on the progression of laser-induced CNV, several studies in mice have reported that systemic or intraocular delivery of β-AR antagonists causes a reduction in CNV lesion size ( Lavine et al, 2013 , 2017 ; Nourinia et al, 2015 ; Omri et al, 2019 ). Lavine et al (2013) measured lesion areas (as opposed to volumes) 14 days after laser photocoagulation and found that daily intraperitoneal injection of propranolol (20 mg/kg/day) led to a 50% reduction in lesion size.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that lncRNA plays an important role in triggering EMT in epithelial cells during tumor metastasis [ 14 , 15 ]. MALAT1 can promote the proliferation, migration, and epiretinal membrane formation of RPE cells in PVR [ 16 , 17 ]. In addition, it was confirmed that downregulation of MALAT1 could inhibit the induction of EMT by TGF-β1 in ARPE-19 cells, and significantly reduced the upregulation of EMT-related transcription factors Snail, SLUG, and ZEB1 in RPE cells [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%